2002
DOI: 10.1300/j064v20n02_05
|View full text |Cite
|
Sign up to set email alerts
|

Mulching Practice in a Semi-Arid Zone of Nigeria for Soil Erosion Control and Grain Yield of Maize

Abstract: Water erosion is a major factor degrading soils of the Nigerian semi-arid ecoregions, and making agriculture less sustainable. For example, soil erosion in the Northern Guinea savanna ecozones of Nigeria is prominent in cultivated areas during the early part of the rain-fed crop production season, when most soil surfaces are bare. In order to estimate the magnitude and timing of soil loss from cultivated lands. Selected herbaceous legumes (Macrotyloma uniflorum, Stylosanthes hamata and Mucuna pruriens) were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In contrast, the reduced canopy cover provided by the thin and vertical structure of the Palma cactus gives limited protection to the soil surface and limited rainfall interception [5,6,8,9]. When comparing mulch cover to cover crop for soil erosion control in a semiarid zone of Nigeria, Odunze [31] observed that the better erosion control obtained under straw was attributed to the fact that straw was uniformly spread over the soil surface, and it was close to the soil surface when compared to cover crop whose canopy was further above the soil surface. Mulch cover increases the hydraulic roughness and friction slope of the soil surface, therefore retarding surface flow and enhancing infiltration [7,13].…”
Section: Coir Dust and Palma Cactus For Soil And Water Conservationmentioning
confidence: 99%
“…In contrast, the reduced canopy cover provided by the thin and vertical structure of the Palma cactus gives limited protection to the soil surface and limited rainfall interception [5,6,8,9]. When comparing mulch cover to cover crop for soil erosion control in a semiarid zone of Nigeria, Odunze [31] observed that the better erosion control obtained under straw was attributed to the fact that straw was uniformly spread over the soil surface, and it was close to the soil surface when compared to cover crop whose canopy was further above the soil surface. Mulch cover increases the hydraulic roughness and friction slope of the soil surface, therefore retarding surface flow and enhancing infiltration [7,13].…”
Section: Coir Dust and Palma Cactus For Soil And Water Conservationmentioning
confidence: 99%
“…Organic and non-organic mulches, if available, cut down runoff and erosion world wide in cropped fields and plantations [123][124][125][126][127][128].…”
Section: Ground Protectionmentioning
confidence: 99%
“…To reverse this trend and enhance soil fertility and improve crop productivity, conservation agriculture (CA) is often promoted (Ito et al, ; Valbuena et al, ; Corbeels et al, ). Direct‐seeding and no‐tillage cropping systems are being developed to sustainably improve crop productivity and soil fertility (Odunze, ; Razafimbelo et al, ; Saito et al, ). These systems offer several advantages: they are less time consuming, require less arduous work, reduce weeding and improve crop yields (Odunze, ; Salako & Tian, ).…”
Section: Introductionmentioning
confidence: 99%
“…Amzad Hossain *Correspondence to: Abib Camara, National School of Agriculture, Thies-University, Km 3,5 Route de Khombole, PO Box A 296 Thies, Senegal. Email: camouabib@yahoo.fr are being developed to sustainably improve crop productivity and soil fertility (Odunze, 2002;Razafimbelo et al, 2006;Saito et al, 2010). These systems offer several advantages: they are less time consuming, require less arduous work, reduce weeding and improve crop yields (Odunze, 2002;Salako & Tian, 2003).…”
Section: Introductionmentioning
confidence: 99%